The Role of Financial Data Processing and Application in Strengthening National Financial Supervision - Shaofu Zhu (Innovation in Science and Technology, 2024)
This study focuses on the role of financial data processing and application in strengthening national financial supervision. It begins by discussing the background and significance, purpose and methods of studying this topic in the digital age. The theoretical foundations of financial data processing and application are introduced in detail, including the concept and characteristics of financial data, related theories of data processing and application, and the objectives and principles of financial supervision. The current status and challenges of financial data utilization in national financial supervision are analyzed. The multifaceted role of financial data processing and application in strengthening financial supervision is explored in depth, such as improving the transparency of fiscal fund use, accurately identifying problems and risks, optimizing budget management, and improving the performance evaluation system. Strategies for using financial data analysis to strengthen budget management and performance evaluation are proposed, including establishing and improving financial data collection and management systems, using data analysis tools for budget management, and building data analysis models for performance evaluation. The importance of financial data in maintaining national financial security and stability is emphasized, including preventing financial risks and ensuring sustainable fiscal development. Experiences, lessons, and insights are summarized and enlightened through the analysis of successful and problematic cases. Finally, the study is concluded with an outlook on the future application of financial data in financial supervision, including aspects such as technological development, system construction, talent cultivation, and data sharing.